Post-warmup strategies to maintain body temperature and physical performance in professional rugby union players - West, D. J.; Russell, M.; Bracken, R. M.; Cook, C. J.; Giroud, T.; Kilduff, L. P. (Journal of Sports Sciences, 2016)
We compared the effects of using passive-heat maintenance, explosive activity or a combination of both strategies during the post-warmup recovery time on physical performance. After a standardised warmup, 16 professional rugby union players, in a randomised design, completed a counter-movement jump (peak power output) before resting for 20 min and wearing normal-training attire (CON), wearing a passive heat maintenance (PHM) jacket, wearing normal attire and performing 3 × 5 CMJ (with a 20% body mass load) after 12 min of recovery (neuromuscular function, NMF), or combining PHM and NMF (COMB). After 20 min, participants completed further counter-movement jump and a repeated sprint protocol. Core temperature (Tcore) was measured at baseline, post-warmup and post-20 min. After 20 min of recovery, Tcore was significantly lower under CON and NMF, when compared with both PHM and COMB (P < 0.05); PHM and COMB were similar. Peak power output had declined from post-warmup under all conditions (P < 0.001); however, the drop was less in COMB versus all other conditions (P < 0.05). Repeated sprint performance was significantly better under COMB when compared to all other conditions. Combining PHM with NMF priming attenuates the post-warmup decline in Tcore and can positively influence physical performance in professional rugby union players.